Alterations in the oral microbiome of individuals with a healthy oral environment following COVID-19 vaccination - Osamu Uehara; Yoshihiro Abiko; Toshiyuki Nagasawa; Tetsuro Morikawa; Daichi Hiraki; Fumiya Harada; Yutaka Kawano; Seiko Toraya; Hirofumi Matsuoka; Durga Paudel; Shintaro Shimizu; Koki Yoshida; et al. (BMC, 2022)
Abstract Background Several reports suggest that the microbiome of the digestive system affects vaccine efficacy and that the severity of coronavirus disease (COVID-19) is associated with decreased diversity of the oral and/or intestinal microbiome. The present study examined the effects of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine on the oral microbiome. Methods Forty healthy Japanese oral healthcare personnel were recruited, and unstimulated saliva was collected before vaccination, after the 1st vaccination, and after the 2nd vaccination. Genomic DNA was extracted from saliva samples, and PCR amplicons of the 16S rRNA gene were analyzed using next-generation sequencing. Microbial diversity and composition were analyzed using Quantitative Insights into Microbial Ecology 2. In addition, alterations in microbial function were assessed using PICRUSt2. Results SARS-CoV-2 mRNA vaccination significantly increased oral bacterial diversity and significantly decreased the proportion of the genus Bacteroides. Conclusions The SARS-CoV-2 mRNA vaccine alters the oral microbiome; accordingly, vaccination might have beneficial effects on oral health.